Controlling nematode infections in sheep: application of HACCP. Issue 8 (5th October 2018) - Gascoigne, Emily; Morgan, Eric Rene; Lovatt, Fiona; Vineer, Hannah Rose
Abstract : Gastrointestinal nematode infection in sheep is a significant challenge for production with implications for animal health and welfare, and lamb growth. Flocks rely on the chemical control of worm burdens, but with the increasing challenge of anthelmintic resistance there is a necessity for farmers to uptake SCOPs (Sustainable Control of Parasites) guidance. Vets need to communicate practical strategies to farmers and suggest novel approaches that address these challenges so that holistic and sustainable parasite management can be achieved. This article examines the challenge of nematode infections and anthelmintic resistance and suggests how hazard analysis and critical control point (HACCP) application may facilitate a whole‐flock strategy.